Pre-operative parameters do not reliably identify post-operative respiratory risk in children undergoing adenotonsillectomy - Thavagnanam, Surendran; Cheong, Saou Yinn; Chinna, Karuthan; Nathan, Anna Marie; De Bruyne, Jessie Anne (Wiley, 2017)
Aim: Adenotonsillectomy is performed in children with recurrent tonsillitis or obstructive sleep apnoea. Children at risk of post-operative respiratory complications are recommended to be monitored in paediatric intensive care unit (PICU). The aim of the study is to review the risk factors for post-operative complications and admissions to PICU. Methods: A review of medical records of children who underwent adenotonsillectomy between January 2011 and December 2014 was performed. Association between demographic variables and post-operative complications were examined using chi-square and Mann–Whitney tests. Results: A total of 214 children were identified, and of these, 19 (8.8%) experienced post-operative complications. Six children (2.8%) had respiratory complications: hypoxaemia in four and laryngospasm requiring reintubation in a further two. Both of the latter patients were extubated upon arrival to PICU and required no escalation of therapy. A total of 13 (6.1%) children had non-respiratory complications: 8 (3.7%) had infection and 5 (2.3%) had haemorrhage. A total of 26 (12.1%) children were electively admitted to PICU and mean stay was 19.5 (SD ± 13) h. No association between demographic characteristics, comorbid conditions or polysomnographic parameters and post-operative complications were noted. A total of 194 (90.7%) children stayed only one night in hospital (median 1 day, range 1–5 days). Conclusion: The previously identified risk factors and criteria for PICU admission need revision, and new recommendations are necessary.